1992
DOI: 10.1002/jsfa.2740580102
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationship of nitrogen nutrition with maize (Zea mays) grain yield, nitrogen use efficiency and grain quality

Abstract: Eight maize (Zea mays L) hybrids were grown under five N levels with or without the nitrification inhibitor, nitrapyrin (2-chloro-[6-trichloro-methyl] pyridine), to evaluate N interactions relative to yield performance, N use efficiency, grain protein concentration, and kernel texture. Results indicate that maize hybrids can be grouped into three categories based on grain yield: (1) low N-responsive types which reach their maximum yield with 134 kg ha-' of applied N ; (2) intermediate types that respond to mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
3

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 26 publications
(9 reference statements)
1
43
0
3
Order By: Relevance
“…5 illustrated the similar scenario that amino acid decreased with the increase of protein in jute seed. Tsai et al (1992) reported that protein content increased from applied nitrogen which was accompanied by an increase in the amount of zein present in the endosperm. Increase in zein content in endosperm reduces the lysine and tryptophan concentrations, thus reducing the total free amino acid.…”
Section: Resultsmentioning
confidence: 99%
“…5 illustrated the similar scenario that amino acid decreased with the increase of protein in jute seed. Tsai et al (1992) reported that protein content increased from applied nitrogen which was accompanied by an increase in the amount of zein present in the endosperm. Increase in zein content in endosperm reduces the lysine and tryptophan concentrations, thus reducing the total free amino acid.…”
Section: Resultsmentioning
confidence: 99%
“…It has been generally agreed that despite the mobile nature of N, a source that releases N slowly when the crop is not in need, and that makes it available when the crop is growing fast and assimilation is at its peak would improve uptake and efficiency. Tsai et al (1992) suggested the use of ammonium-N (NH 4 -N) fertilizers can reduce leaching and denitrification losses and allow extended availability for late season uptake. Several researchers demonstrated this by quantifying the benefit of NH 4 based N sources (Wang and Below, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Maize growing is influenced by many environmental factors (Wolf and Van Diepen, 1995;Olesen and Bindi, 2002;Kovačević et al, 2009;Olesen et al, 2011), management systems (Tsai et al, 1992;Tolk et al, 1999;Pandey et al, 2000;Kirda et al, 2005;Josipović et al, 2012) and genetic factors. Clark et al (1999), Abbas et al (2005), Hammad et al (2012) and Azizian and Speaskhah (2014) have stated that amount of plant available water and nitrogen are the most important factors for plant production.…”
Section: Introductionmentioning
confidence: 99%